Modelling plant yield and quality response of fresh-market spinach (Spinacia oleracea L.) to mineral nitrogen availability in the root zone - Massa, Daniele; Incrocci, Luca; Botrini, Luca; Carmassi, Giulia; Diara, Cecilia; Delli Paoli, Pasquale; Incrocci, Giorgio; Maggini, Rita; Pardossi, Alberto (Italian Journal of Agronomy, 2018)
Spinach is one of the most important green-leafy vegetables, consumed worldwide, and its intake is beneficial for human beings. In this crop, produce yield and quality are closely related to plant nitrogen (N) nutrition. A precise supply of N is also essential for high environmental and economic sustainability. Main aims of the work were: i) to establish relationships between produce yield or quality and mineral N availability in the root zone; and ii) to define an optimal mineral N level to be maintained in the root zone for spinach. Eight experiments were carried out during a four-year-long period under typical Mediterranean climate conditions. Different amounts of N fertilisers were supplied leading to twenty different levels of mineral N in the root zone. Experimental measurements included climate parameters, plant growth, tissue and soil analyses, produce yield and quality indicators. A segmented linear model significantly represented the relationship between crop yield (1.7 to 21.7 t ha–1) and soil mineral N concentration (7.6 to 41.0 mg kg–1). Basing on this model, an optimal mineral N threshold was fixed at 23.4 mg kg–1. Above this threshold, crop yield did not show any significant variations as well as tissue characteristics and produce quality. Plants grown under suboptimal N levels showed reduction in growth, tissue mineral (nutrients) content, and SPAD index. The proposed models could be implemented in fertilisation protocols for the optimization of N supply and the estimation of spinach growth and yield.